Building a knowledge society: information needs and information problems in rural areas and urban informal settlements in Bangladesh - Iqbal, Nasim (The Research Centre and Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2003)
The present study argues that information is a key determinant of community empowerment. The objective of the research is to identify how information can influence development in the developing countries, especially in Bangladesh, a country currently in the early stages of shifting towards a more information-based society. Fieldwork already undertaken in Bangladesh by the researcher has shown that there have been some major changes in the economic and social life of people who live in the rural and urban informal settlements due to the influence of information in the last few decades. There are a good number of sources and agents involved in dissemination of information and knowledge in rural and urban informal settlements of Bangladesh but people in these areas question the relevance and appropriateness of some of the services offered, because such services does not always satisfy the demand of information of local residents. As a result, the experience developed has not been widely disseminated and taken up by them. This study considers primarily the demand side, focusing on the information needs of residents in rural and poor urban settlements, and the sources they use in accessing that information. The study also examines the problem areas of accessing information encountered by those residents. Finally, it is hoped the study will result in a model for the dissemination of information services in rural areas and urban informal settlements of Bangladesh.